Polarization tunable, multicolor emission from core-shell photonic III-V semiconductor nanowires. - Mokkapati, S; Saxena, D; Jiang, N; Parkinson, P; Wong-Leung, J; Gao, Q; Tan, H; Jagadish, C (2012)
We demonstrate luminescence from both the core and the shell of III-V semiconductor photonic nanowires by coupling them to plasmonic silver nanoparticles. This demonstration paves the way for increasing the quantum efficiency of large surface area nanowire light emitters. The relative emission intensity from the core and the shell is tuned by varying the polarization of the excitation source since their polarization response can be independently controlled. Independent control on emission wavelength and polarization dependence of emission from core-shell nanowire heterostructures opens up opportunities that have not yet been imagined for nanoscale polarization sensitive, wavelength-selective, or multicolor photonic devices based on single nanowires or nanowire arrays.